Guinness World Records 2001 - Guinness World Records (England Guinness World Records Ltd., 2001)
The ultimate snapshot of this amazing world! Over 1,000 extraordinary new records, more than 300 stunning full-color pictures. Completely updated section on computer games, the internet, special effects, martial arts, dance music the prehistoric world and much more.
Includes Colored Illustrations and Index.
Keywords: Curiosities and Wonders -- World Records